STRATEGIC APPROACHES TO CONSTRUCTING A PERSONNEL REWARD SYSTEM IN THE CONTEXT OF HR POLICY TRANSFORMATION - ZELENA, Mariya; VOLIANSKA-SAVCHUK, Lesya; POVKH, Ivan (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article substantiates strategic approaches to building an effective personnel reward system in the context of transforming human resource (HR) policy. It emphasizes that motivation and reward mechanisms play a key role in ensuring organizational success by linking employees’ personal goals with corporate objectives. Based on theoretical generalizations and analysis of modern trends, the study reveals that digitalization, changing labor values, and competition for talent require a shift from traditional, standardized remuneration models to flexible, personalized systems that combine material and non-material incentives. The reward system is interpreted as an integral element of motivational policy that enhances productivity, loyalty, and engagement while shaping a favorable corporate culture. The authors propose a conceptual model of reward management based on the principles of fairness, transparency, differentiation, and adaptability. Attention is given to the interaction between motivation policy and the overall business strategy, highlighting the need for alignment with innovation, development, and leadership goals. The paper classifies strategies of labor motivation—those focused on employee development, quality of working life, innovation, and competitiveness—and identifies their influence on staff behavior and enterprise performance. Practical recommendations are presented for constructing an adaptive system of rewards that responds to internal organizational culture and external market changes. The article concludes that a well-designed reward system enhances the efficiency of human resource management, supports sustainable development, reduces staff turnover, and strengthens the company’s strategic potential. A comprehensive and flexible reward mechanism, integrating financial and intangible components, ensures long-term employee engagement, satisfaction, and organizational competitiveness under conditions of dynamic transformation.
Keywords: personnel management strategy; reward system; employee motivation; HR policy; management transformation; staff incentives; managerial approaches; labor motivation; human resource strategy; organizational development